Symbolic shapes in Alaa Bashir's drawings (a study in meaning and form) (Journal of the College of Basic Education, 2022)
The research deals with the symbolic shapes in Alaa Bashir's drawings, and it consists of four chapters. And its most important artists, then the chapter concludes with the indicators of the theoretical framework, then touches on the third chapter represented by the research procedures, then selecting the sample and analyzing it, and concludes with the fourth chapter represented by the most important results and conclusions